2001
DOI: 10.1021/jm0005048
|View full text |Cite
|
Sign up to set email alerts
|

Highly Potent and Subtype Selective Ligands Derived byN-Methyl Scan of a Somatostatin Antagonist

Abstract: The search for synthetic peptide analogues of somatostatin (SRIF) which exhibit selective affinities for the five known receptor subtypes (sst1-5) has generated a large number of potent agonists. Some of these agonists display good subtype selectivities and affinities for the subtypes 1, 2, 3, and 5, including analogues created by N-methyl amino acid substitutions in a standard octapeptide analogue format. We have now extended this peptide backbone N-methylation approach to a potent somatostatin receptor antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 31 publications
(55 reference statements)
2
49
0
Order By: Relevance
“…We examined two compounds, both of which have been reported to behave as sst2 antagonists. Confirming previous results (Rajeswaran et al, 2001), Coy-14 did not inhibit cAMP production in our experiments (data not shown). Furthermore, it did not induce sst2A receptor internalization and instead blocked agonist stimulation (Figs.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We examined two compounds, both of which have been reported to behave as sst2 antagonists. Confirming previous results (Rajeswaran et al, 2001), Coy-14 did not inhibit cAMP production in our experiments (data not shown). Furthermore, it did not induce sst2A receptor internalization and instead blocked agonist stimulation (Figs.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to agonists, the sst2 antagonists Coy-14 (Rajeswaran et al, 2001) and CYN-154806 (Bass et al, 1996) did not induce receptor endocytosis in either CHO-sst2 cells (Fig. 4) or HEK-sst2 cells (data not shown).…”
Section: Effect Of Sst2 Agonists and Antagonists On Receptormentioning
confidence: 83%
See 1 more Smart Citation
“…In fact, in some cases the N ␣ -methyl group can significantly increase the biological potency. 30,31 There are several strategies to synthesize the N ␣ -methyl amino acid. Considering the Fmoc protection of amino acids, we have selected the reported method 32 so that the N ␣ -Fmoc is orthogonally protected (Scheme 1).…”
Section: Synthesis Of N ␣ -Fmoc-n ␣ -Methyl Amino Acid Precursorsmentioning
confidence: 99%
“…]Bn(6 -14), because this analog has been shown to be metabolically stable and to have high affinity and potency for activating all Bn receptor subtypes (Mantey et al, 1997;Pradhan et al, 1998;Ryan et al, 1998a,b;Reubi et al, 2002;Moody et al, 2004). This approach was used because it has successfully yielded highly selective peptide ligands with a number of other receptors (Reissmann et al, 1996;Pradhan et al, 1998;Rajeswaran et al, 2001 (6 -14) that were N-terminally truncated or had selective substitutions, because this was reported to result in increasing selectivity for one type of Bn receptor in a recent study (Darker et al, 2001). The final approach used was to synthesize various shortened , ␤Ala ]Bn (6 -14) analogs recently reported to be selective for a Bn receptor subtype and fully characterize them pharmacologically by binding studies and assays assessing receptor activation at each of the three human Bn receptor subtypes.…”
mentioning
confidence: 99%